Defoliation intensity and performance of soybean plants with different growth habits - Monteiro, Manoela Andrade; Koch, Felipe; Nobre, Felipe Luiz de Lemos; Zulli, Felipe Santos; Araújo, Bruno Oliveira Novais; Borges, Eduardo Golçalves; Pedó, Tiago; Aumonde, Tiago Zanatta; dos Santos, Esmael Lopes (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: 'Helvetica',sans-serif; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';" lang="EN-US">The objective of this work was to evaluate the influence of the level of artificial defoliation, applied in stages V6 and R2, on the quality and yield components of soybean seeds. The experiment was conducted in a greenhouse in the municipality of Cascavel, Paraná State, Brazil. The experimental design was a randomized block with four replications, in a 5 x 2 x 2 factorial scheme (five levels of defoliation x two cultivars, two phenological stages (V6: fifth fully developed trifoliolate leaf and R2: full flowering), two growth habits). The analyzed variables were mass of 100 seeds, number of pods per plant, seed number per plant, seed number per pod, germination, dry matter of seedlings and length of shoot and roots of seedlings. Defoliation above 50% results in the reduction of the number of pods and seeds per plant to grow indeterminate growth and reduction in the mass of 100 seeds for cultivars of determined growth.